2019
DOI: 10.1097/pcc.0000000000001882
|View full text |Cite
|
Sign up to set email alerts
|

Development of the Pediatric Extracorporeal Membrane Oxygenation Prediction Model for Risk-Adjusting Mortality*

Abstract: Objective: To develop a prognostic model for predicting mortality at time of extracorporeal membrane oxygenation (ECMO) initiation for children which is important for determining centerspecific risk-adjusted outcomes.Design: Multivariable logistic regression using a large national cohort of pediatric ECMO patients. Setting:The intensive care units of the eight tertiary care children's hospitals of the Collaborative Pediatric Critical Care Research Network Patients: 514 children (< 19 years), enrolled with an i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 37 publications
(39 reference statements)
1
20
0
Order By: Relevance
“…Bailly et al depicted comparable mortality between pediatric patients and neonates confirming our results . Also the working group by Alsoufi et al revealed fine long‐term survival rates in patients who survived the first 30 days after ECMO treatment .…”
Section: Discussionsupporting
confidence: 89%
“…Bailly et al depicted comparable mortality between pediatric patients and neonates confirming our results . Also the working group by Alsoufi et al revealed fine long‐term survival rates in patients who survived the first 30 days after ECMO treatment .…”
Section: Discussionsupporting
confidence: 89%
“…The strengths of the study is that the analysed cohort had a good representation of various diagnosis cohorts, the different types of ECMO support and a nearly identical distribution of the PEP-model based risk categories as the original derivation study. 3 Given the limitations pointed out, our findings should be considered exploratory and this study on its own does not invalidate the PEP-model. A multicentre study with much higher sample size may be useful to confirm our findings and could also lead to an impetus to improve the model if these findings are confirmed.…”
Section: Discussionmentioning
confidence: 85%
“…The strengths of the study is that the analysed cohort had a good representation of various diagnosis cohorts, the different types of ECMO support and a nearly identical distribution of the PEP-model based risk categories as the original derivation study. 3…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Concerning most aspects of ECMO outcome (patient safety, resource utilization, quality, morbidity, mortality), there is concensus that ECMO is best provided at high-volume ECMO centers (810). However, case mix may influence survival data (11), and Bailly et al found no association between center size and outcome (12). As recently as a decade ago, only a small number of centers worldwide provided mobile ECMO services for bedside assessment and cannulae insertion.…”
Section: Introductionmentioning
confidence: 99%